Polyethylene terephthalate/clay nanocomposites with polyhedral oligomeric silsesquioxane as dispersant - Toh, Joan Cher Ling (2012)
Polyethylene terephthalate (PET)/clay nanocomposite is an attractive high performance material that can be used for demanding applications due to its potential to exhibit superior properties at low clay loadings. However, organoclays do not have the adequate thermal stability to withstand the high temperatures required for processing PET and this limits the complete exfoliation of the organoclays and ultimately the properties and applications of the resultant nanocomposites. In order to overcome the degradation issues of the organic surfactants, the thesis focuses on two approaches, i.e. (1) to incorporate thermal stable polyhedral oligomeric silsesquioxane (POSS) into the PET/clay system to replace conventional organic surfactants, and (2) to completely do away with organic surfactant and prepare PET/clay nanocomposites with surfactant-free clay. In this work, the preparation of PET/clay nanocomposites using POSS compounds either as a surfactant (POSS-imidazolium salt) or a spacer (trisilanolphenyl POSS, Tsp-POSS) was investigated. In particular, the resultant structures and properties of the nanocomposites were evaluated in the areas of the extent of clay dispersion, thermo-mechanical properties and thermo-oxidative properties.